Suatu Riset Empiris Mengenai Hubungan Manajemen Resiko Kredit, Ukuran, Profitabilitas Serta Kepemilikan Bank-Bank Di BEI - Hambali, Denny (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study investigates the relationship between bank size, profitability, and ownership to excess capital for credit risk management (CRM) in banks operating in Indonesia. Using data from 52 banks listed on the Indonesia Stock Exchange (IDX) over the period 2020 to 2023, a panel regression analysis model was applied to evaluate the relationship between these variables. The results show that bank size has a significant relationship with excess capital; larger banks tend to have more capital to manage credit risk. This finding is in line with the theory that large banks have more capacity to cope with market fluctuations and risks associated with lending. On the other hand, profitability does not show a positive and significant relationship with excess capital. This may be due to the fact that banks that highly prioritize profitability may tend to allocate their capital into more profitable investments, instead of keeping capital reserves for risk management. In addition, managerial ownership also does not show a significant relationship with excess capital. This indicates that decisions and strategies taken by managers do not necessarily contribute to strengthening capital reserves to address credit risk. This study confirms the importance of bank size and profitability in strengthening credit risk management in banks listed on the IDX. Larger bank size can provide better stability in risk management, while good profitability can help in strengthening the capital position.